Recovery, Rehabilitation, and Return to Full Duty in a Military Population After a Recent Injury: Differences Between Lower-Extremity and Spine Injuries - Daniel I. Rhon, P.T., D.Sc., Ph.D; Deydre S. Teyhen, P.T., Ph.D; Kyle Kiesel, P.T., Ph.D; Scott W. Shaffer, P.T., Ph.D; Stephen L. Goffar, P.T., Ph.D; Tina A. Greenlee, Ph.D; Phillip J. Plisky, P.T., D.Sc (Elsevier, 2022)
Purpose: To compare readiness to return to duty in soldiers following recent lower-extremity versus spine injury. The secondary purposes were to provide normative data for the Selective Functional Movement Assessment Top Tier movements (SFMA-TTM) and assess the association between SFMA-TTM scores and future injury occurrence, comparing injuries of the lower extremity and thoracic/lumbar spine. Methods: SFMA was rated by trained assessors on 480 U.S. Army soldiers within 2 weeks of being cleared to return to duty after recent lower-extremity or lumbar/thoracic injury. Participants were followed for 1 year to determine incidence of subsequent time-loss injury. Results: Only 74.4% of soldiers felt 100% mission capable when returning to full duty (73.6% lower-extremity; 76.5% spine). After 1 year, 37.9% had sustained a time-loss injury, and pain with movement at baseline was associated with higher odds for having an injury (odd ratio 1.53 95% confidence interval 1.04-2.24; P = .032). Almost all (99.8%) had at least 1 dysfunctional pattern, and 44.1% had pain with at least 1 movement (40.3% with previous lower-extremity injury; 54.6% with previous spine injury) after being cleared to return to duty. Conclusions: One in four patients did not feel 100% mission capable upon being cleared for full duty. Pain with movement was also associated with future injury. Regardless of recent injury type, 99.8% of soldiers returned to full unrestricted duty with at least 1dysfunctional movement pattern and 44.1% had pain with at least 1 of the SFMA-TTM movements. Level of Evidence: Level III, retrospective comparative cohort study.